2022
DOI: 10.3390/healthcare10050917
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Abdominal Microcurrent in the Consumption and Proportion of Energy Substrates during Aerobic Exercise: A Pilot Study

Abstract: Microcurrent therapy can increase lipolytic activity. However, it is unknown if the increased availability of lipids can influence the selection of energy substrates during a single session of aerobic exercise. We aimed to analyze the effect of microcurrent application to the abdominal region in the consumption of lipids and carbohydrates, and respiratory exchange ratio (RER) during a single session of moderate aerobic exercise in young adults. A pilot study was conducted in which participants were allocated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Nevertheless, the results obtained in EG can be explained by the mechanism of fatty acids' oxidation induced by HIIT, which promotes a global reduction of body fat. (19) The unusual results found in the participants of MEG, for the parameter "functionality of the lumbar spine", may be related to the capacity of MES to stimulate the intracellular metabolism by supplying protons and electrons, leading to depolarization of the membrane and increasing the levels of adenosine triphosphate (ATP) (20,21) .This ATP, synthesized by specific enzymes, may be used as an energy source for various biological processes in the body, such as muscle contraction (22) .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the results obtained in EG can be explained by the mechanism of fatty acids' oxidation induced by HIIT, which promotes a global reduction of body fat. (19) The unusual results found in the participants of MEG, for the parameter "functionality of the lumbar spine", may be related to the capacity of MES to stimulate the intracellular metabolism by supplying protons and electrons, leading to depolarization of the membrane and increasing the levels of adenosine triphosphate (ATP) (20,21) .This ATP, synthesized by specific enzymes, may be used as an energy source for various biological processes in the body, such as muscle contraction (22) .…”
Section: Discussionmentioning
confidence: 99%
“…The microcurrent protocol was set at an intensity between 700 and 999 μA with frequencies of 10-25 Hz (Noites et al 2017). Conversely, a recent study reported no acute lipolytic effect of a pre-exercise MCT protocol set at 1000 μA intensity in young university students (Vilarinho et al 2022). On the other hand, MCT was implemented in young physically active individuals (men and women aged 27.2 ± 3.6 years) before and after endurance exercise (Piras et al 2021).…”
Section: Effects Of Microcurrent When Combined With Endurance Exercisementioning
confidence: 99%
“…Although both groups (MCT and placebo) showed significant increases ( p < 0.01) and large effect sizes ( d = 2.75 and 2.5 respectively) in the exercise-induced serum glycerol levels that were used as lipolysis marker indicating triglycerides hydrolysis (Lafontan and Langin 2009 ), the elevated values measured in the MCT group were meaningful compared to those measured in the placebo group (+ 0.15 ± 0.09 vs. 0.09 ± 0.07 mmol/l, p = 0.03). However, more recently, compared to a sham treatment ( n = 20), no lipolytic effect was observed in response to a 40 min application of MCT ( μA at 10 and 25 Hz) prior to 50 min of moderate-intensity endurance exercise ( n = 18) in university students (Vilarinho et al 2022 ). Further studies, using larger sample sizes, similar to those used by Noites et al ( 2017 ) (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation